Redesign of the transport system of banana bunches for field harvesting Case study: Studer Innotec - Ordoñez-Avila, Jose Luis (2019)
This paper describes the experience of technological integration in the case study of Studer Innotec, company that manufactures inverters / chargers and regulators in Switzerland, using an inverter / charger to redesign the transport system improving the efficiency of the agro-productive chain of the post-harvest of banana, developed in the Atlantic sector of Honduras. Currently, the banana transport system is carried out via cable using load animals (mules) making a slow process, in addition to generating costs for the care of these animals or by machines uploaded to the cable via a diesel combustion engine coupled to an oil pump, which generate emissions of gases that pollute the environment and even the banana itself.With the aim of integrating industrial equipment that allows to collect a larger number of bunches than in the current system, ensuring the quality properties of the banana is presented the redesign of a machine used to transport the banana, changing its diesel engine of 9 hp, by a 5-hp three-phase motor, where the greatest challenge has been to pass the electric energy stored in batteries by an inverter, until reaching a frequency inverter, which controlled the torque and speed of the motor, allowing a better use of the motor, with which it has been possible to transport more than 70 bunches of banana in a route greater than 800 meters inside the farm.